2015
DOI: 10.1061/(asce)gt.1943-5606.0001211
|View full text |Cite
|
Sign up to set email alerts
|

Design of Stable Concave Slopes for Reduced Sediment Delivery

Abstract: Constructed slopes are traditionally given a planar form. However, natural slopes are more likely to be concave in cross section. In addition, laboratory and computational studies have demonstrated that concave slopes yield less sediment than planar slopes. With current autoguided construction equipment, it is now possible to construct slopes with concave profiles and a more natural appearance, yet a simple method to describe such concave slopes for a given level of mechanical stability does not exist. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Consequently, when MCO = 0, Y e = 0. However, in concave slopes the critical failure surface may emerge above the toe (i.e., Y e > 0) and such possibility needs to be considered (Utili and Nova 2007;Jeldes et al 2014 the results for a planar profile (i.e., MCO/H = 0). This Case results in the least stable (highest N value) and no reduction in volume (∆A/H 2 = 0) as shown in Fig.…”
Section: Solution Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, when MCO = 0, Y e = 0. However, in concave slopes the critical failure surface may emerge above the toe (i.e., Y e > 0) and such possibility needs to be considered (Utili and Nova 2007;Jeldes et al 2014 the results for a planar profile (i.e., MCO/H = 0). This Case results in the least stable (highest N value) and no reduction in volume (∆A/H 2 = 0) as shown in Fig.…”
Section: Solution Proceduresmentioning
confidence: 99%
“…Engineered slopes and earth structures are commonly built with a planar profile in cross section. However, it has been shown that concave slopes offer higher stability (e.g., Sokolovskiĭ 1960; Utili and Nova 2007;Jeldes et al 2013) and better erosion resistance (e.g., Rieke-Zapp and Nearing 2005;Schor and Gray 2007;Jeldes et al 2014) when compared with the equivalent planar slopes. Utili and Nova (2007) demonstrated the higher stability of concave slopes and argued that such higher stability may also explain the concave shape of perimeter walls of some typical Japanese castles (Nishida et al 2005;Utili and Nova 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some log-spiral concave surface may be more stable than a planar profile (Utili and Nova, 2007). Concave slopes may also have superior erosion resistance compared to planar slopes (Young and Mutchler, 1969a, Young and Mutchler, 1969b, Meyer and Kramer, 1969, Rieke-Zapp and Nearing, 2005, Schor and Gray, 2007 making them preferable within many embankments and cuttings (Jeldes et al, 2014a, Jeldes et al, 2014b. However, there is limited ability to address their stability without resorting to computational tools.…”
Section: Introductionmentioning
confidence: 99%